Online Learning Readiness in Facing the Covid-19 Pandemic at MTS Manunggal Sagara Ilmi, Deli Serdang, Indonesia - Nur Afrianti; Reza Aditia (AIBPM Publisher, 2020)
The Covid-19 pandemic has affected all aspects, especially in the field of education. Schools have been required to do online learning, while not all schools are ready to implement it. This study aims to determine the readiness of online learning for students at MTs Manunggal Sagara Ilmi in terms of parents' occupation, ownership of cellphones, laptops, tablets, internet costs incurred, and sources of the internet access used for online learning. The sampling technique used purposive sampling with the division of classes VII, VIII, and IX. From the various characteristics used to identify samples, it can be concluded that the Learning Management System (LMS) cannot be fully implemented in MTS Manunggal.